Delayed surgery among patients diagnosed with spinal disorders: Retrospective analysis. - Linda S Aglio; Tayisha Examond; Samuel A Justice; Laura Mendez-Pino; Elisabetta Mezzalira; Leah A Baez; Nicole J Kelly-Aglio; Kara G Fields; Robert N Jamison; Robert R Edwards; Sarah M Corey (PLoS ONE)
To determine the association between race and access to healthcare services with respect to the treatment of spinal cord disorders, a retrospective cohort study of patients receiving an initial diagnosis, two Boston hospitals, September 1, 2017, to June 1, 2018, follow-up through December 31, 2019. Data from patients (18-89 years) diagnosed with spinal cord disorders were extracted retrospectively from a centralized database. Kaplan-Meier curves and multivariable Cox proportional hazards models analyzed the time to spine surgery following initial diagnosis. Patient race was the primary explanatory variable, with five racial groups (Asian, Black, Hispanic, Other, and White) based on a combination of their self-reported race and ethnicity. Hispanic ethnicity (regardless of race), non-Hispanic ethnicity (designated Asian, Black, or White), and "Other" (non-Hispanic patients who designated their race as other than Asian, Black, or White; this included American Indian, Alaska Native, Native Hawaiian or other Pacific Islander, or two or more races). Among 56,186 patients (4% Asian, 7% Black, 5% Hispanic, 6% Other, 77% White) meeting inclusion criteria, Asian (hazard ratio (HR) 0.67 (0.55, 0.82)), Black (HR 0.55 (0.47, 0.63)), Hispanic (HR 0.43 (0.35, 0.52)), and Other (HR 0.59 (0.51, 0.69)) patients had significantly longer times to surgery compared with White patients.